Early maladaptive schemas and emotional dependence in battered women and no battered women in the city of Lima - Huerta, Rosa (2017)
The study submitted to the analysis of the following variables: early maladaptive schemas and emotional dependence in function to the presence or not of violence in a sample of 385 women battered women and no battered, who were given a sociodemographic survey, the Young Schema Questionnaire (YSQ-S3) composed of 18 schemes and the Emotional Dependence Inventory. It was found that there is a significant and positive correlation between dimensions and early maladaptive schemes with factors of emotional dependency, compounded by the presence of violence in the relationship (sig. = 0.01) which is an indicator of latent risk in the sample examined because it facilitates the permanence in a dysfunctional and violent relationship with a partner as well as a high risk of their mental health. In addition, mayor relationship between emotional dependence and early maladaptive schemes, when there is violence Dimensions of schemes are more affected. It was also found significant differences between the two groups. The presence of violence in the couple relationship activates the early maladaptive schemes and produce syndromes and mental disorders in the women.